18. Durations of Antibiotic Therapy and Factors Associated with Longer Than Recommended Durations for Common Ambulatory Infections in an Integrated Healthcare System. (31st December 2020) - Deida, Axel Vazquez; Shihadeh, Katherine C; Aragon, Deborah; Knepper, Bryan C; Jenkins, Timothy C
Abstract: Background: Duration of antibiotic therapy is an important focus for antibiotic stewardship, but the extent and drivers of excessive durations are not well understood. This project aimed to describe durations of therapy prescribed for common infections across the ambulatory care settings of an integrated healthcare system and identify factors associated with longer than recommended durations. Methods: This was a retrospective, cross-sectional evaluation conducted from July 1, 2018 to June 30, 2019. We identified antibiotic prescriptions for adults age 18 years or older presenting to a Denver Health ambulatory care facility (urgent care, emergency department, family medicine clinic, or internal medicine clinic) for an infection with a recommended duration of therapy of 5 days or less based on institutional guidance. Infections included purulent and non-purulent cellulitis, uncomplicated subcutaneous abscess, acute bacterial sinusitis (ABS), acute otitis media (AOM), community acquired pneumonia, cystitis, and pyelonephritis treated with an indicated fluoroquinolone. Prescriptions for more than 5 days were classified as longer than recommended. We evaluated whether the following factors were associated with longer than recommended prescriptions: location of visit, type of infection, patients' age, race/ethnicity, sex, infection type, and prescribing provider type Results: 5331 prescriptions met inclusion criteria. Of those, the duration of therapy was longer than recommended for 2095 (39%) (Table 1). Durations varied significantly across locations (p< 0.0001). In the sub-group analysis family medicine clinics had the highest proportion of longer than recommended durations (46%). Durations also varied significantly by type of infection. For cellulitis, ABS, and AOM, the duration was longer than recommended in 50%, 54%, and 75% of cases, respectively. Other factors associated with longer than recommended durations included male sex (p< 0.0001) and prescriptions by advanced practice providers (p = 0.0008). Table 1: Antibiotic Duration of Therapy for Common Outpatient Infections Conclusion: Care locations, infection types, and both patient and prescriber factors were associated with longer than recommended prescriptions suggesting specific opportunities to prevent excessive durations of therapy. Disclosures: All Authors : No reported disclosures